(3eQGLYI GdeYdheGJ GdeMGSHjI h eSDhdjGJ GdJbQjQs - (3Cejf GdSjO GMeO(B, (3dWajs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2009)
(3eQGLYI OhQI GdGjQGOGJ h GdeJMUdGJ h eQGLYI OhQI GdCLhQ h EOGQI GdehGQO GdHTQjI , eQGLYI OhQI GdeTJQjGJ h GdeOahYGJ , eQGLYI OhQI GdeNRhf h GdeSJhOGYGJ Cj OhQI GdGfJGL h GdJMhjd , eQGLYI OhQI GdGfJGL h GdJMhjd GdCUhd GdKGHJI h GgJdGcGJgG , eQGLYI OhQI GdMUhd Ydi QCS GdeGd h EYGOI GdOaY OhQI GdJehjd , eQGLYI GdCQUOI GdfbOjI h GdGSJKeGQGJ h MSGHGJ eNJGQI CNQi , eQMdI EJeGe h aMU YedjI GdeQGLYI , h CNjQG JbGQjQ GdeQGLYI Gdi eSJNOej GdbhGFe GdeGdjI h GdGOGQIs
Keywords: (3GdJbGQjQ GdeGdjIs; (3GdeMGSHIs; (3eQGLYI GdMSGHGJs